A rapid method for determination of the hydrogen isotopes of H2O in micro‐inclusions by chromium‐filled elemental analyzer/isotope ratio mass spectrometry. (24th April 2019) - Li, Hongwei; Feng, Lianjun
Abstract : Rationale: The study of hydrogen isotopes in fluid inclusions is of great significance in the evolution of ore deposits, speleothem research and fluid migration. Conventional analysis methods are based on off‐line thermal decrepitation or mechanical crushing followed by dual‐inlet isotope ratio mass spectrometry (DI‐IRMS). Because a large sample size (at least 1 g) is required for the conventional methods, the hydrogen isotope analysis of small‐sized quartz samples is challenging. Methods: A method for the hydrogen isotope analysis of H2 O from fluid inclusions in minerals using a Cr‐EA/IRMS method (a single‐oven, chromium‐filled elemental analyzer coupled to IRMS) is presented. The reactor is filled with chromium reagent instead of glassy carbon chips, which allows quantitative conversion of the H2 O in quartz inclusions into H2 for the first time. The hydrogen isotope ratio is then determined by continuous‐flow IRMS. Results: Eight quartz samples were analyzed using the Cr‐EA/IRMS method. The hydrogen isotope ratios obtained using this method were consistent with those obtained using the off‐line method. For small samples of less than 20 mg, the δ 2 H values showed large variance (6–15‰), suggesting that the results were significantly influenced by the background. In contrast, the reproducibility of the δ 2 H values for samples of more than 20 mg was better than 3‰. Conclusions: The proposed Cr‐EA/IRMS method greatly reduces the minimum sample size (to ca 20 mg) and the laboratory time (30 samples each day) without compromising precision compared with the off‐line method. The method offers a reliable and economic approach for measuring the δ 2 H values of geological samples.